Assessment of the feed additive consisting of red carotenoid‐rich Paracoccus carotinifaciens NITE SD 00017 for salmon and trout for the renewal of its authorisation (ENEOS Techno Materials Corporation) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on red carotenoid‐rich Paracoccus carotinifaciens NITE SD 00017 for salmon and trout (category: sensory additives; functional group: colourants; substances which when fed to animals add colours to food of animal origin) for the renewal of its authorisation. The applicant provided evidence that the additive complies with the conditions of the authorisation. The Panel concludes that the use of the additive in salmon and trout remains safe for the target species, the consumer and the environment under the authorised conditions of use. When assessing consumer exposure to canthaxanthin and adonirubin at the level of the existing maximum residue limits (MRL) for poultry and the proposed MRL for trout/salmon (5 mg/kg muscle), the exposure of consumers exceeds the acceptable daily intake (ADI) in the population classes toddlers and other children. The Panel considers that there is no need to restrict the use of the additive to fish older than 6 months or of more than 50 g. Red carotenoid‐rich Paracoccus carotinifaciens NITE SD 00017 is not irritant to the skin, but is irritant to the eyes. It is considered a dermal and respiratory sensitiser and any exposure via skin or the respiratory tract is a risk.